Electrocoppering solution for filling X-shaped hole of printed circuit and application of electrocoppering solution
通过在X型孔填孔中使用特定配比的电镀铜镀液,包括五水硫酸铜、硫酸、氯化钠和特定的第一类、第二类和第三类添加剂,解决了面铜厚度和凹陷度控制难题,实现了高质量的X型孔填充,提升了电镀添加剂产业的发展。
Patent Information
- Application Number
- CN202411255240.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to effectively control the thickness and recession of surface copper in X-shaped hole filling, resulting in unfavorable subsequent fine line etching. The research on the mechanism of action of the third type additive is relatively scarce, which affects the development of the electroplating additive industry.
Using an electroplating copper plating solution including copper sulfate pentahydrate, sulfuric acid, sodium chloride, and the first, second and third additives. The third additive is 1-methyl-4-nitroimidazole and sulfur Azapine, 6-mercaptopurine, and 2-thioxanthine achieve high-quality X-pore filling through specific electroplating process steps and concentration ratios.
The thickness of the surface copper is controlled less than 13μm and the recession is less than 4μm, which meets industrial production needs and improves the quality and consistency of X-shaped hole filling.
Smart Images

Figure CN119243271A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additives for copper electroplating of printed circuit boards, and in particular relates to a copper electroplating solution for filling X-shaped holes in printed circuits and an application thereof. Background Art
[0002] Printed circuit boards are an indispensable part of electronic devices. Their main function is to integrate various components and realize electrical interconnection between components. With the increase of the integration and number of layers of printed circuit boards, the requirements for the reliability of electrical interconnection are also increasing. The most representative one is the demand for high-quality X-type laser via filling.
[0003] X-type laser through-hole (hereinafter referred to as X-type hole) is a through-hole formed by laser drilling, that is, laser drilling is performed on both sides of the plate to form a through-hole. It has the characteristics of small aperture in the middle and large aperture at the hole mouth. The filling of high-quality X-type holes should meet the following requirements: Under the premise that the thickness of the coating outside the hole does not change much, the hole should be filled with copper without voids, and the surface depression is small or even without obvious depression. The filling process should follow the following steps: First, under the joint action of different additives, the copper deposition rate in the hole is much higher than that outside the hole, especially in the middle position of the X-type hole, where a connecting "bridge" composed of the copper plating layer will be formed first; then, the X-type hole is divided into two structures similar to blind holes. The two blind holes undergo a bottom-up super-filling process under the action of additives, and finally achieve high-quality filling of the X-type hole.
[0004] In the above process, additives play a vital role. The first type of additives, such as polyethylene glycol, can inhibit hydrogen evolution on the surface and reduce surface defects; the second type of additives, such as sodium polydisulfide dipropane sulfonate, is mainly adsorbed in the low mass transfer rate and low current density area such as the pore, and can accelerate the deposition of copper, making the copper deposition rate in the pore larger; the third type of additives, such as Janus Green, is mainly adsorbed in the high current density area, reducing the copper deposition rate outside the pore, and finally achieving high-quality X-type hole filling.
[0005] At present, the development and application of the first and second types of additives are relatively complete, but there is a lack of effective research results on the mechanism of action of the third type of additives. At the same time, the third type of additives has a higher commercial value, so the research and development of the third type of additives will help the development and progress of the electroplating additive industry.
[0006] In the X-type hole filling process, after the X-type hole is fully filled, the surface copper is often too thick, and too thick surface copper is not conducive to the subsequent etching of fine circuits. Figure 1The following is a picture of the effect of a company's current X-type hole filling. After the hole is filled, the surface copper thickness is 16 microns. This surface copper thickness can be further reduced by replacing the third type of additive in the copper plating solution, which is beneficial to the subsequent production of fine circuits.
[0007] For the above reasons, the present invention proposes an additive system that can be applied to high-quality X-type hole copper filling, which can meet the actual needs in printed circuit manufacturing. Summary of the invention
[0008] The object of the present invention is to provide a copper electroplating solution for filling X-shaped holes in printed circuits and its application.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] An electroplating copper plating solution for filling X-shaped holes in printed circuits, characterized in that: the plating solution comprises copper sulfate pentahydrate, sulfuric acid, and sodium chloride, and the additive system comprises a first type of additive, a second type of additive, and a third type of additive;
[0011] The concentration of the copper sulfate pentahydrate is 180g / L-250g / L, the concentration of the concentrated sulfuric acid is 10g / L-80g / L, and the concentration of the sodium chloride is 50mg / L-132mg / L;
[0012] The first type of additive is one or more of polyethylene glycol, polypropylene glycol, and a block copolymer of ethylene oxide and propylene oxide, and the concentration of the first type of additive is 200 mg / L-600 mg / L;
[0013] The second type of additive is one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, sodium phenyl polydisulfide propane sulfonate, and 2-mercaptobenzimidazole, and the concentration of the second type of additive is 1 mg / L-8 mg / L;
[0014] The third type of additives is one or more of 1-methyl-4-nitroimidazole, azathioprine, 6-mercaptopurine, and 2-thioxanthine, and the concentration of the third type of additives is 1 mg / L-8 mg / L.
[0015] As a preferred embodiment, when the plating solution is used for X-type hole filling, the concentration of copper sulfate pentahydrate is 220g / L-250g / L, the concentration of concentrated sulfuric acid is 40g / L-80g / L, and the concentration of sodium chloride is 50mg / L-132mg / L.
[0016] As a preferred embodiment, when the plating solution is used for X-shaped hole filling, the upper and lower apertures of the X-shaped hole filling are 50 μm-80 μm, the middle aperture is 25 μm-40 μm, and the dielectric thickness is 130 μm-170 μm.
[0017] As a preferred embodiment, when the plating solution is used for filling X-shaped holes, the electroplating process includes the following steps:
[0018] Step 1, degreasing, micro-etching and pre-preg treatment of the copper clad laminate with X-shaped holes;
[0019] Step 2: Pour the prepared plating solution into the plating tank, use the copper-clad laminate with X-shaped holes treated in step 1 as the cathode, use soluble phosphor copper as the anode, and use a DC power supply for electroplating, wherein the current density is 1A / dm 2 ~2A / dm 2 , the plating solution temperature is 22±3℃, and the electroplating time is 30~90min.
[0020] Furthermore, the copper sulfate pentahydrate may be replaced by copper sulfate. When copper sulfate is used, the concentration of copper sulfate in the plating solution may be converted according to the same molar concentration of the copper sulfate pentahydrate used above.
[0021] Furthermore, the concentrated sulfuric acid may be replaced by dilute sulfuric acid. When dilute sulfuric acid is used, the concentration of the dilute sulfuric acid in the plating solution may be converted according to the same molar concentration of the concentrated sulfuric acid used above.
[0022] Furthermore, the sodium chloride may be replaced by hydrochloric acid. When hydrochloric acid is used, the concentration of the hydrochloric acid in the plating solution may be converted according to the same molar concentration of the sodium chloride used above.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a plating solution additive system for electroplating copper for filling X-shaped holes in printed circuits. The third type of additive used has a simple molecular structure. The plating solution additive system provided by the present invention is applied to X-shaped hole filling. While achieving high-quality filling effect, the average thickness of the surface copper is controlled to be less than 13μm, and the concavity is less than 4μm. The control ability of the surface copper thickness is in a leading position among similar inventions and existing production technologies. At the same time, the obtained copper surface is smooth and bright, which can meet the needs of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the effect diagram of a company's current X-shaped hole filling;
[0026] Figure 2 This is the metallographic image of the X-shaped hole slice obtained in Example 1;
[0027] Figure 3 This is the metallographic image of the X-shaped hole slice obtained in Example 2; DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0029] The embodiment provides a copper electroplating solution for filling X-shaped holes in printed circuits, the solution comprising copper sulfate pentahydrate, sulfuric acid, and sodium chloride, and the additive system comprising a first type of additive, a second type of additive, and a third type of additive;
[0030] The concentration of the copper sulfate pentahydrate is 180g / L-250g / L, the concentration of the concentrated sulfuric acid is 10g / L-80g / L, and the concentration of the sodium chloride is 50mg / L-132mg / L;
[0031] The first type of additive is one or more of polyethylene glycol, polypropylene glycol, and a block copolymer of ethylene oxide and propylene oxide, and the concentration of the first type of additive is 200 mg / L-600 mg / L;
[0032] The second type of additive is one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, sodium phenyl polydisulfide propane sulfonate, and 2-mercaptobenzimidazole, and the concentration of the second type of additive is 1 mg / L-8 mg / L;
[0033] The third type of additives is one or more of 1-methyl-4-nitroimidazole, azathioprine, 6-mercaptopurine, and 2-thioxanthine, and the concentration of the third type of additives is 1 mg / L-8 mg / L.
[0034] In some embodiments, when the plating solution is used for X-type hole filling, the concentration of copper sulfate pentahydrate is 220g / L-250g / L, the concentration of concentrated sulfuric acid is 10g / L-80g / L, and the concentration of sodium chloride is 50mg / L-132mg / L.
[0035] In some embodiments, when the plating solution is used for X-shaped hole filling, the upper and lower hole diameters of the X-shaped hole filling are 50 μm-80 μm, the middle hole diameter is 25 μm-40 μm, and the medium thickness is 130 μm-170 μm.
[0036] In some embodiments, when the plating solution is used for filling X-shaped holes, the electroplating process includes the following steps:
[0037] Step 1, degreasing, micro-etching and pre-preg treatment of the copper clad laminate with X-shaped holes;
[0038] Step 2: Pour the prepared plating solution into the plating tank, use the copper-clad laminate with X-shaped holes treated in step 1 as the cathode, use soluble phosphor copper as the anode, and use a DC power supply for electroplating, wherein the current density is 1A / dm 2 ~2A / dm 2 In some embodiments, the plating solution has a temperature of 22±3° C. and a plating time of 30 to 90 min.
[0039] When the plating solution is used for electroplating, the electroplating process comprises the following steps:
[0040] Step 1, degreasing, micro-etching and pre-preg treatment of the copper clad laminate with X-shaped holes;
[0041] Step 2: Pour the prepared plating solution into the plating tank, use the copper-clad laminate with X-shaped holes treated in step 1 as the cathode, use soluble phosphor copper as the anode, and use a DC power supply for electroplating, wherein the current density is 1A / dm 2 ~2A / dm 2 , the plating solution temperature is 22±3℃, and the electroplating time is 30~90min.
[0042] Example 1
[0043] In the plating solution for filling the X-shaped holes of the printed circuit board in Example 1, the base plating solution is: copper sulfate pentahydrate with a concentration of 240 g / L, concentrated sulfuric acid with a concentration of 30 g / L, and sodium chloride with a concentration of 66 mg / L;
[0044] Polyethylene glycol 8000 was used as the first type of additive at a concentration of 500 mg / L;
[0045] Sodium polydisulfide dipropane sulfonate was used as the second type of additive at a concentration of 2 mg / L;
[0046] 6-Mercaptopurine was used as the third type of additive at a concentration of 2 mg / L.
[0047] The plating solution is used for an X-shaped hole with an upper and lower hole diameter of 60 μm, a middle hole diameter of 30 μm, and a dielectric layer thickness of 140 μm.
[0048] The printed circuit provided in Example 1 is used in an X-type hole filling process, which specifically includes the following steps:
[0049] Step 1: Prepare the plating solution:
[0050] 1.1 Evenly mix copper sulfate pentahydrate, concentrated sulfuric acid and sodium chloride to obtain 1.5L of basic plating solution; wherein the concentration of copper sulfate pentahydrate is 240g / L, the concentration of concentrated sulfuric acid is 30g / L, and the concentration of sodium chloride is 66mg / L;
[0051] 1.2 Add polyethylene glycol 8000 as the first type of additive, sodium polydisulfide propane sulfonate as the second type of additive, and thiopurine as the third type of additive to the basic plating solution obtained in step 1.1, and mix them evenly to obtain a plating solution; finally, the concentration of polyethylene glycol 8000 is 500 mg / L, the concentration of sodium polydisulfide propane sulfonate is 2 mg / L, and the concentration of 6-mercaptopurine is 2 mg / L;
[0052] Step 2: Pre-treating the copper clad laminate with X-shaped holes, including degreasing, micro-etching and pre-preg;
[0053] 2.1 Oil removal:
[0054] The degreasing liquid is composed of 20 g / L sodium hydroxide, 1 g / L sodium dodecylbenzene sulfonate, 3 g / L sodium carbonate, 5 g / L trisodium phosphate dodecahydrate and deionized water, and then the copper clad board with X-shaped holes is immersed in the degreasing liquid for 5 minutes;
[0055] 2.2 Micro-etching:
[0056] The micro-etching solution is composed of 5% sulfuric acid, 5% sodium persulfate and deionized water, and then the copper-clad board obtained after the treatment in step 2.1 is immersed in the micro-etching solution for 30 seconds;
[0057] 2.3 Pre-preg:
[0058] The pre-dip solution is composed of 5% sulfuric acid and deionized water, and then the copper clad laminate obtained after the treatment in step 2.2 is immersed in the pre-dip solution for 5 minutes;
[0059] Step 3: X-shaped hole electroplating copper filling:
[0060] Pour the plating solution prepared in step 1 into the plating tank, and directly put the copper-clad laminate with X-shaped holes after pretreatment in step 2 into the middle of the plating tank and fix it as the cathode. Soluble phosphor copper is used as anode plates on both sides, and a DC power supply is used for electroplating, wherein the current density is 1.5A / dm 2 , the plating solution temperature is 22±3℃, the air stirring speed is 1L / min, and the electroplating time is 60min.
[0061] The electroplated copper-clad board obtained in step 3 was washed with water and then blown dry, sliced and observed and photographed under a metallographic microscope. The depression and surface copper thickness were measured, where the depression refers to the depth of the depression from the copper outside the hole to the center of the hole, and the surface copper thickness refers to the thickness of the chemical copper plating layer from the copper outside the hole to the outside of the hole.
[0062] Figure 2The longitudinal cross-sectional view of the X-shaped hole in Example 1 after being filled with electroplating is observed using a metallographic microscope; the measurement results show that the upper surface depression of the X-shaped hole obtained by using this formula is too high. After analysis, it is believed that this is caused by the low content of the second type of additive, which leads to slower copper growth in the hole. Therefore, the concentration of the second type of additive should be appropriately increased.
[0063] Example 2
[0064] In the plating solution for filling the X-shaped holes of the printed circuit board in Example 2, the base plating solution is: copper sulfate pentahydrate with a concentration of 220 g / L, concentrated sulfuric acid with a concentration of 50 g / L, and sodium chloride with a concentration of 99 mg / L;
[0065] Ethylene oxide and propylene oxide block copolymer was used as the first type of additive, with a concentration of 500 mg / L;
[0066] Sodium 3-mercapto-1-propane sulfonate was used as the second type of additive at a concentration of 3 mg / L;
[0067] Azathioprine is used as the third type of additive at a concentration of 2 mg / L. The plating solution is used for an X-shaped hole with an upper and lower aperture of 60 μm, a middle aperture of 30 μm, and a dielectric layer thickness of 140 μm.
[0068] The printed circuit provided in Example 2 is used in an X-type hole filling process, which specifically includes the following steps:
[0069] Step 1: Prepare the plating solution:
[0070] 1.1 Evenly mix copper sulfate pentahydrate, concentrated sulfuric acid and sodium chloride to obtain 1.5L of basic plating solution; wherein the concentration of copper sulfate pentahydrate is 220g / L, the concentration of concentrated sulfuric acid is 50g / L, and the concentration of sodium chloride is 99mg / L;
[0071] 1.2 Add ethylene oxide and propylene oxide block copolymer as the first type of additive, add sodium 3-mercapto-1-propane sulfonate as the second type of additive, and add thiopurine as the third type of additive to the basic plating solution obtained in step 1.1, mix them evenly, and obtain a plating solution; finally, the concentration of ethylene oxide and propylene oxide block copolymer is 500 mg / L, the concentration of sodium 3-mercapto-1-propane sulfonate is 3 mg / L, and the concentration of thiopurine is 2 mg / L;
[0072] Step 2: Pre-treating the copper clad laminate with X-shaped holes, including degreasing, micro-etching and pre-preg;
[0073] 2.1 Oil removal:
[0074] The degreasing liquid is composed of 20 g / L sodium hydroxide, 1 g / L sodium dodecylbenzene sulfonate, 3 g / L sodium carbonate, 5 g / L trisodium phosphate dodecahydrate and deionized water, and then the copper clad board with X-shaped holes is immersed in the degreasing liquid for 5 minutes;
[0075] 2.2 Micro-etching:
[0076] The micro-etching solution is composed of 5% sulfuric acid, 5% sodium persulfate and deionized water, and then the copper-clad board obtained after the treatment in step 2.1 is immersed in the micro-etching solution for 30 seconds;
[0077] 2.3 Pre-preg:
[0078] The pre-dip solution is composed of 5% sulfuric acid and deionized water, and then the copper clad laminate obtained after the treatment in step 2.2 is immersed in the pre-dip solution for 5 minutes;
[0079] Step 3: X-shaped hole electroplating copper filling:
[0080] Pour the plating solution prepared in step 1 into the plating tank, and directly put the copper-clad laminate with X-shaped holes after pretreatment in step 2 into the middle of the plating tank and fix it as the cathode. Soluble phosphor copper is used as anode plates on both sides, and a DC power supply is used for electroplating, wherein the current density is 1.5A / dm 2 , the plating solution temperature is 22±3℃, the air stirring speed is 1L / min, and the electroplating time is 60min.
[0081] The electroplated copper-clad board obtained in step 3 was washed with water and then blown dry, sliced and observed and photographed under a metallographic microscope. The depression and surface copper thickness were measured, where the depression refers to the depth of the depression from the copper outside the hole to the center of the hole, and the surface copper thickness refers to the thickness of the chemical copper plating layer from the copper outside the hole to the outside of the hole.
[0082] Figure 3 The longitudinal cross-sectional view of the X-shaped hole in Example 2 after electroplating is observed using a metallographic microscope; the measurement results show that the depression of the X-shaped hole obtained by using this formula does not exceed 4μm, and the average surface copper thickness does not exceed 13μm. Figure 3 Compared with the current manufacturing level of a certain company in China, the two have similar levels in terms of concavity, and are leading in the control of surface copper thickness; compared with the additive system used in the existing patent of the same type "an organic additive for filling holes and copper electroplating solution for MSAP", the average surface copper thickness that can be obtained is 21μm, which is much higher than the average surface copper thickness of the X-shaped hole obtained in Example 2.
[0083] The above embodiments are preferred implementation methods of the present invention, and are used to illustrate the present invention, but the present invention is not limited to the specific details in the above embodiments. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A copper electroplating solution for filling X-shaped holes in printed circuits, characterized in that: The plating solution includes copper sulfate pentahydrate, sulfuric acid, and sodium chloride, and the additive system includes a first type of additive, a second type of additive, and a third type of additive; The concentration of the copper sulfate pentahydrate is 60g / L-250g / L, the concentration of the concentrated sulfuric acid is 10g / L-240g / L, and the concentration of the sodium chloride is 50mg / L-132mg / L; The first type of additive is one or more of polyethylene glycol, polypropylene glycol, and a block copolymer of ethylene oxide and propylene oxide, and the concentration of the first type of additive is 200 mg / L-600 mg / L; The second type of additive is one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, sodium phenyl polydisulfide propane sulfonate, and 2-mercaptobenzimidazole, and the concentration of the second type of additive is 1 mg / L-8 mg / L; The third type of additives is one or more of 1-methyl-4-nitroimidazole, azathioprine, 6-mercaptopurine, and 2-thioxanthine, and the concentration of the third type of additives is 1 mg / L-8 mg / L.
2. The electroplating copper solution for filling X-shaped holes in printed circuits according to claim 1, characterized in that: When the plating solution is used for X-type hole filling, the concentration of copper sulfate pentahydrate is 220g / L-250g / L, the concentration of concentrated sulfuric acid is 10g / L-80g / L, and the concentration of sodium chloride is 50mg / L-132mg / L.
3. The copper plating solution for X-shaped holes in printed circuits according to claim 1, characterized in that: When the plating solution is used for filling X-shaped holes, the upper and lower hole diameters of the X-shaped holes are 50 μm-80 μm, the middle hole diameter is 25 μm-40 μm, and the medium thickness is 130 μm-170 μm.
4. The use of the copper electroplating solution according to any one of claims 1 to 3, characterized in that: It can be used to fill copper in X-shaped holes to achieve interconnection electroplating.
5. The use of the copper electroplating solution according to claim 4, characterized in that: When the plating solution is used for filling X-shaped holes, the electroplating process includes the following steps: Step 1, degreasing, micro-etching and pre-preg treatment of the copper clad laminate with X-shaped holes; Step 2: Pour the prepared plating solution into the plating tank, use the copper-clad laminate with X-shaped holes treated in step 1 as the cathode, use soluble phosphor copper as the anode, and use a DC power supply for electroplating, wherein the current density is 1A / dm 2 ~2A / dm 2 , the plating solution temperature is 22±3℃, and the electroplating time is 30~90min.
Citation Information
Cited By
X-shaped hole rapid filling electroplating process and device and electroplating liquid
CN120050872A
Plating solution for thick copper electroplating of ceramic substrate and use method of plating solution
CN120250092A